2015
DOI: 10.1111/jac.12127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO2 Enrichment and Drought on Photosynthesis, Growth and Yield of an Old and a Modern Barley Cultivar

Abstract: Susceptibility of crops to drought may change under atmospheric CO 2 enrichment. We tested the effects of CO 2 enrichment and drought on the older malting barley cultivar Golden Promise (GP) and the recent variety Bambina (BA). Hypothesizing that CO 2 enrichment mitigates the adverse effects of drought and that GP shows a stronger response to CO 2 enrichment than BA, plants of both cultivars were grown in climate chambers. Optimal and reduced watering levels and two CO 2 concentrations (380 and 550 ppm) were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 69 publications
4
27
0
Order By: Relevance
“…In terms of the CO 2 fertilization effect, Kimball (1983), Chang et al (2016), Kim et al (2016) and Schmid et al (2016) stated that as CO 2 level increased, vegetation yield changed, and the change was however related to the environment conditions such as light, soil nutrient and soil moisture and temperature. We assume that the CO 2 fertilization effects can be reflected from the changes in photosynthesis and net primary productivity.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the CO 2 fertilization effect, Kimball (1983), Chang et al (2016), Kim et al (2016) and Schmid et al (2016) stated that as CO 2 level increased, vegetation yield changed, and the change was however related to the environment conditions such as light, soil nutrient and soil moisture and temperature. We assume that the CO 2 fertilization effects can be reflected from the changes in photosynthesis and net primary productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Results of these measurements are given in Schmid et al . (). Plant development was reported using the BBCH code (Meier, ).…”
Section: Methodsmentioning
confidence: 99%
“…Schmid et al . () have investigated growth, yield, and photosynthetic parameters in the same experiment as ours with barley and found that CO 2 fertilization compensated for the negative effect of drought on grain yield and water‐use efficiency, especially in one of the two cultivars tested. Here, we present results from root exudation analyses to gain information on responses of the hidden half of barley plants.…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthesis and growth in C3 plants are often enhanced by eCO 2 resulting in a higher yield, which has been observed for many crops [2]. The magnitude of yield response has been shown to vary between different crops [3] and crop varieties [4,5], but also to depend on differences in experimental systems [6]. It has been argued that yield stimulation is overestimated due to unrealistic growing conditions in enclosure systems, including open-top chambers (OTCs) [7,8].…”
Section: Introductionmentioning
confidence: 99%